2020
DOI: 10.3390/f11030342
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Bark and Ambrosia Beetles Associated with Imported Non-Coniferous Wood and Potential Horizontal Phytosanitary Measures

Abstract: Many bark and ambrosia beetle species (Coleoptera: Scolytinae and Platypodinae) are known to have spread worldwide in relation to international trade. Concerns have been expressed within the European and Mediterranean Plant Protection Organization (EPPO) about recent introductions of non-indigenous species of these groups. Regulation of the non-coniferous wood trade into many EPPO member countries is currently not sufficient to cover such risks. In 2018-2019, an EPPO study on the risk of bark and ambrosia beet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 18 publications
2
31
0
1
Order By: Relevance
“…There is no doubt that the PSHB attacks may cause tree mortality on certain host trees (Hulcr and Dunn, 2011;Mendel et al, 2017;Paap et al, 2018;Coleman et al, 2019). However, the concept of attacks on "healthy" trees is often debated in the literature, as trees that appear healthy may have been previously exposed to some stress (Grousset et al, 2020). Keler (1956) defined primary insects as "those which prefer completely healthy plants in full vigor"; based on this definition, Rudinsky (1962) suggested that most species of bark and ambrosia beetles must be considered secondary insects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no doubt that the PSHB attacks may cause tree mortality on certain host trees (Hulcr and Dunn, 2011;Mendel et al, 2017;Paap et al, 2018;Coleman et al, 2019). However, the concept of attacks on "healthy" trees is often debated in the literature, as trees that appear healthy may have been previously exposed to some stress (Grousset et al, 2020). Keler (1956) defined primary insects as "those which prefer completely healthy plants in full vigor"; based on this definition, Rudinsky (1962) suggested that most species of bark and ambrosia beetles must be considered secondary insects.…”
Section: Discussionmentioning
confidence: 99%
“…Although healthy trees are normally unsuitable to attack by bark and ambrosia beetles, some species are reported to attack and eventually kill live, apparently healthy non-coniferous trees, but this represents a minority of species to date (Grousset et al, 2020). Among the ambrosia-feeding scolytids, Xyleborini are the most numerous and widely distributed tribe.…”
Section: Introductionmentioning
confidence: 99%
“…Scolytinae are xylophagous beetles colonizing the wood at phloem (phleophagous species) or xylem level (xylomycetophagous species) of many ornamental and forest plants (Kirkendall and Biedermann 2015 ). In recent years, Europe and the Americas have been affected by the introduction and establishment of numerous exotic species of the Xyleborini tribe, which caused growing concerns for native biodiversity and forest resources (Kirkendall and Faccoli 2010 ; Grousset et al 2020 ). Their ability to escape phytosanitary controls due to their cryptobiotic behaviour, their capacity to establish in the new environment due to their reproductive behavior, their large polyphagy and the increasing global trade of wood (Reed and Muzika 2010 ; Rassati et al 2016a ; Smith et al 2020 ) make Xyleborini a potentially invasive taxon.…”
Section: Introductionmentioning
confidence: 99%
“…In Somerset West in the Western Cape, PSHB spread at least 3 km from the putative point of introduction in only three months, and in the opposite direction of the prevailing winds (F Roets pers obs). Natural spread is therefore substantial, but the longdistance spread of PSHB is enabled by the ease of movement of infested wood and planting material (Grousset et al 2020). As a developing country, a large proportion of households in South Africa are heavily dependent on wood for their energy needs (Shackleton 2018), presenting a probable pathway for long-distance spread (Fig.…”
Section: Discussionmentioning
confidence: 99%